Commercial Insurance Triples Chances of Breast Cancer Survival in a Public Hospital. Issue 6 (9th September 2013) - Shi, Runhua; Mills, Glenn; McLarty, Jerry; Burton, Gary; Shi, Zhenzhen; Glass, Jonathan
Abstract Breast cancer survival is affected both by endogenous factors and exogenous factors such as socioeconomic status. This study explored the relationship between insurance status and overall survival of 987 female breast cancer patients in a population served by a public hospital. All patients were offered the same level of care regardless of ability to pay. Of the 987 breast cancer patients investigated, 54.6% were African‐American. 54.1% of patients were insured (commercial insurance or Medicare), 27.1% with Medicaid, and 18.8% who were uninsured. Overall median survival was 15.5 years and was not statistically significant between Caucasian and African‐American women. Median survival times were 15.8, 11.3, and 8.2 years for insured, Medicaid, and uninsured groups, respectively. Uninsured patients had worse overall survival rates compared with insured patients (p < 0.05). Adjusting for other factors (e.g., stage, age, race, body mass index, and income), insurance was a significant factor affecting survival with hazard ratios of 2.24 and 3.22 for Medicaid and uninsured patients, respectively, compared with insured patients. Even in a public hospital, after adjusting for potential risk factors, insurance status still proved to be an important factor in the survival of breast cancer patients. Further research is necessary to identify causal factors related to the survival disparities associated with insurance status.